Comparative analysis of antimicrobial resistance and genetic diversity of Bordetella bronchiseptica isolates obtained from swine within the United States - Nicholson, Tracy L.; Shore, Sarah M. (Frontiers in Microbiology, 2024)
IntroductionBordetella bronchiseptica is bacterial pathogen that is pervasive in swine populations and serves multiple roles in respiratory disease.MethodsThis study utilized whole-genome sequencing (WGS) analysis to assess the sequence type (ST), identify the genetic diversity of genes predicted to encode regulatory and virulence factors, and evaluated any potential antimicrobial resistance harbored by B. bronchiseptica isolates obtained from swine within the U.S.ResultsWhile a generally high degree of genomic conservation was observed among the swine B. bronchiseptica isolates, genetic diversity was identified within the fimNX locus and among the sequence type six (ST6) isolates. The majority of B. bronchiseptica isolates exhibited phenotypic resistance to four antibiotic classes, however, only three antimicrobial resistance genes were identified.DiscussionCombined the data suggests that B. bronchiseptica isolates are not serving as a source of antimicrobial resistance gene transference in the swine production environment.